Baiting location affects anticoagulant rodenticide exposure of non‐target small mammals on farms. Issue 2 (22nd July 2020) - Walther, Bernd; Geduhn, Anke; Schenke, Detlef; Schlötelburg, Annika; Jacob, Jens
Abstract: BACKGROUND: Commensal rodents such as Norway rats ( Rattus norvegicus Berk.), black rats ( R. rattus L.) and house mice ( Mus musculus L.) damage stored produce and infrastructure, cause hygienic problems and transmit zoonotic pathogens to humans. The management of commensal rodents relies mainly on the use of anticoagulant rodenticides (ARs). ARs are persistent and bio‐accumulative, which can cause exposure of non‐target species. We compared the baiting strategies to use brodifacoum (BR) in bait boxes indoors only versus in and around buildings in replicated field trials at livestock farms to assess resulting BR residues in non‐target small mammals. RESULTS: When bait was used indoors only, the percentage of trapped non‐target small mammals with BR residues as well as BR concentration in liver tissue was about 50% lower in comparison to bait application in and around buildings. These effects occurred in murid rodents and shrews but not in voles that were generally only mildly exposed. During the baiting period, BR concentration in murids was stable but decreased by about 50% in shrews. CONCLUSION: Restricting the application of BR bait to indoors only can reduce exposure of non‐target species. The positive effect of this baiting strategy on non‐target species needs to be balanced with the need for an effective pest rodent management within a reasonable time. More research is needed to clarify which management approaches strike this balance best. Abstract : When rodenticidal bait was used on farms indoors only versus in and around buildings, anticoagulant rodenticide residues were less prevalent and liver tissue concentrations were lower in non‐target small mammals. © 2020 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.